2011
DOI: 10.1016/j.respe.2011.02.103
|View full text |Cite
|
Sign up to set email alerts
|

Gender and age disparities in the associations of occupational factors with alcohol abuse and smoking in the French working population

Abstract: Background. -This study assessed the associations of short-term employment, physical and psychological occupational demands, and job dissatisfaction with alcohol abuse (using the Audit-C test) and daily smoking among working French men and women in different age groups.Methods. -The sample included 13,241 working people, 18-29, 30-39, and 40-59-years-old, randomly selected in France and interviewed by phone. Occupation, type of employment, physical demands, psychological demands, job dissatisfaction, gender, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
1
16
1
1
Order By: Relevance
“…Similarly, the self-medication hypothesis by Khantzian (2003) could serve as explanation for highrisk consumption patterns amongst disadvantaged occupational groups. There is also evidence that short-term employment is associated with an increased risk for problematic alcohol and tobacco use as well as dependence (Legleye, Baumann, Peretti-Watel, & Chau, 2011). In this context, and with regard to our findings yielding an increased risk for alcohol and cannabis use amongst marginally employed males (results are close to significance; see Tables 3 and 4), it seems to be important to include additional indicators of working conditions in the analyses (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…Similarly, the self-medication hypothesis by Khantzian (2003) could serve as explanation for highrisk consumption patterns amongst disadvantaged occupational groups. There is also evidence that short-term employment is associated with an increased risk for problematic alcohol and tobacco use as well as dependence (Legleye, Baumann, Peretti-Watel, & Chau, 2011). In this context, and with regard to our findings yielding an increased risk for alcohol and cannabis use amongst marginally employed males (results are close to significance; see Tables 3 and 4), it seems to be important to include additional indicators of working conditions in the analyses (e.g.…”
Section: Discussionsupporting
confidence: 62%
“…This pointed the role of cumulative effect of a number of hazards that affected most miners. The injuries were generally directly related to the tasks and those hazards with increasing tiredness or improper posture had higher risks of injury (data not shown) [13]. These findings were expected as most of the miners IJOMEH 2013;26(6)…”
Section: Discussionmentioning
confidence: 89%
“…Year after year, worldwide, this phenomenon is a commonplace for workers, which results in high injury rates for demanding tasks. The injury risk can also be influenced by individuals' characteristics such as social stratification factors including low education, lower socio-occupational category, younger or older age, unhealthy behaviors (smoking, alcohol misuse, obesity, lack of leisure physical and sports activity), altered health status, sleep disorders, mental disorders, and chronic diseases [2][3][4][5][9][10][11][12][13][14][15]. During the last 2 decades research studies have shown that these factors influence the injury risk through physical/mental capacity, knowledge, experience, risk perception, and perceived prevention benefits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A insatisfação no trabalho foi o principal fator entre os ho mens jovens (odds ratio ajustado para abuso de álcool e tabagismo: 1,71 e 2,02), en quanto o emprego em curto prazo foi o principal fator entre mulheres jovens (1,69 e 1,58), sendo esse padrão revertido em gerações mais velhas. Isso equivale a dizer que os trabalhadores com emprego em curto prazo e com altas demandas ocupacionais estão sujeitos a um maior risco de abuso de álcool e tabagismo com altas disparidades de gênero e idade (Legleye, Baumann, PerettiWatel, Beck, & Chau, 2011).…”
Section: Uso De Substâncias E Trabalhounclassified